Sustainability, Ethics, and Authenticity in Indigenous Tourism: The Case of Eskasoni Cultural Journeys on Goat Island - Maher, Patrick T.; MacPherson, Stephanie; Doucette, Mary Beth; Tulk, Janice Esther; Menge, Tracy (Journal of Aboriginal Economic Development)

(untitled) (Captus Press, 2018)
Cape Breton Island (Nova Scotia, Canada) is well known as an island tourism destination, recognized for its rich natural beauty, as well as cultural and heritage products. Eskasoni First Nation is the largest of the five Mi’kmaw communities located on Unama’ki (Cape Breton Island), and until recently Mi’kmaw communities were not recognized as a significant part of the Cape Breton tourism product mix. Tourism as a means of encouraging economic development is not uncommon internationally, and while tourism growth has been significant on the island, questions remain regarding its ethics and authenticity in relation to community economic development. This paper explores the development of an Indigenous (Mi’kmaw) cultural heritage ecotourism product through a community-led approach. Using Eskasoni Cultural Journeys as a case study, the research presented in this paper questions sustainability through the lens of triple bottom line (TBL) accounting, which looks at economic, social, and environmental aspects of development, as well as ethical business practices, such as authenticity and community well-being.